Magnetic Solid-Phase Extraction Using Fe3O4@SiO2 Magnetic Nanoparticles Followed by UV-Vis Spectrometry for Determination of Paraquat in Plasma and Urine Samples. (17th July 2017) - Sha, Ou; Wang, Yu; Yin, Xin; Chen, Xiaobing; Chen, Li; Wang, Shujun
Abstract : A rapid and simple method was optimized and validated for the separation and quantification of paraquat, a frequently used herbicide and a leading cause of fatal poisoning worldwide, at trace levels with UV-Vis spectrophotometry in plasma and urine samples by direct magnetic solid-phase extraction. Fe3 O4 @SiO2 nanoparticles (NPs) were used as the magnetic solid-phase extraction agents and the paraquat absorbed on NPs was eluted using NaOH and ascorbic acid. Upon optimization, paraquat could be extracted and concentrated from various samples by 35-fold. The linear range, limit of detection (LOD), correlation coefficient (R ), and relative standard deviation (RSD) could reach 15.0–400.0  μ g/L, 12.2  μ g/L, 0.9987, and 0.65% (n = 5, c = 40.0  μ g/L), respectively. The Fe3 O4 @SiO2 NPs could be reused up to five times. The method was successfully applied to the determination of paraquat in urine and plasma at different hemoperfusion numbers in a local hospital for the patient of paraquat poisoning. The experiment result could not only enable immediate medical intervention but also benefit patients' survival.